Eye movements among female taekwondo players with high and low level - Elsawy, G. Y. (World Journal of Sport Sciences, 2011)
Sports vision is conceived as a group of techniques directed to preserve and improve the visual function with a goal of enhancing sports performance through a process, which involves teaching the visual behavior required for different sporting activities. The aim of this study was to determine the differences between high level and low level in saccadic adaptation among female taekwondo players. Ten taekwondo players (high level) from Zagazig University team were participated in the study (mean age 21.20 ± 1.32). Ten taekwondo players (low level) were participated in the study (mean age20.46 ± 0.91) and test results were obtained for saccadic eye movements. All participants were female. Results showed that there were no significant differences between high level and low level of female taekwondo players in saccadic adaptation. The researcher concluded that future research should consider these results and determines the vision tests which strong connect with taekwondo game.